SAT0165 Cortical Breaks and Bone Erosions in the Hand Joints: A Cadaver Study Comparing Conventional Radiography with High-Resolution and Micro-Computed Tomography. (10th June 2014) - Scharmga, A.; van Tubergen, A.; van den Bergh, J.; de Jong, J.; Peters, M.; van Rietbergen, B.; Geusens, P.
Abstract : Background: Conventional radiography (CR) is considered the gold standard for diagnosing bone erosions in rheumatic diseases. However, High-Resolution peripheral Quantitative Computed Tomography (HR-pQCT) and microCT (μCT) allow analysis of bone erosions in finger joints at micro level. Objectives: To evaluate cortical breaks and erosions in 16 hand joints imaged by CR, HR-pQCT and μCT. Methods: Eight female human cadaveric index fingers with unknown medical history were scanned by HR-pQCT (82 μm, XtremeCT, Scanco Medical AG, Switzerland) and μCT (18μm, μCT 80, Scanco Medical AG, Switzerland). Also radiographs were taken. A modified SPECTRA (Study grouP for xtrEme Computed Tomography in Rheumatoid Arthritis) algorithm was used by one reader to assess all cortical breaks and all erosions. A cortical break was defined as an interruption of cortical bone on two consecutive slices on two orthogonal planes on HR-pQCT, and similarly, but on eight consecutive slices, for the μCT. Erosion was defined as a definite cortical break, with irregular shape, and loss of underlying trabecular bone on two consecutive slices on two orthogonal planes for HR-pQCT, and eight consecutive slices on two orthogonal planes for μCT. CRs were independently scored for erosions by two rheumatologists. Descriptives and intraclass correlation coefficients (ICC) were calculated. Results: In total, eight metacarpal phalangeal (MCP), four proximal interphalangeal (PIP) and four distal interphalangeal joints of 16 cadaveric index fingers (mean ± SD age 82.6±9.1 years) were imaged by HR-pQCT and μCT. In total, 123 cortical breaks were detected on HR-pQCT (7.0±2.7 per joint) and 237 on μCT (14.5±5.0 per joint). A total of 24 erosions were detected on HR-pQCT (1.3±1.0 per joint) and 72 on μCT (4.0±2.6 per joint). The ICC for total number of cortical breaks was 0.399 (p=0.056), and for number of erosions -0.142 (p=0.706). On CR, twelve joints, eight MCPs and four PIPs, were scored. The total number of erosions scored on CR was four by Reader 1, and two by Reader 2. On the same joints, 16 and 45 erosions were scored on HR-pQCT and μCT, respectively. Conclusions: HR-pQCT detected four times more erosions than CR. The μCT detected even three times more erosions than HR-pQCT. Furthermore, almost twice the number of cortical breaks was scored on μCT than HR-pQCT. These results indicate that further research, such as histological and longitudinal studies, will be necessary to reveal the prevalence, incidence and significance of cortical breaks and erosions as found by HR-pQCT and μCT of hand joints. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1851